Investigation of ZrO[2] and TiO[2] Coatings Influence on Hydrogen Sorption Behavior by Zirconium Alloy Zr1%Nb at Saturation from Gas Atmosphere - Chernov I. P. Ivan Petrovich; Pushilina N. S. Natalia Sergeevna; Kudiyarov V. N. Victor Nikolaevich; Berezneeva E. V. Ekaterina Vladimirovna; Nikolaeva A. N.; Krysina O. V. (Materials Science and Technologies, 2015)
Title screen